INFLUENCE OF LINING THERMAL PERFORMANCE IN ELECTRIC-ARC FURNACES ON POWER CONSUMPTION - S.. V. Korneev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents an analysis of specific features of lining thermal performance in electric-arc furnaces at various technological periods. It has been  shown that on the basis of mathematical modeling methods for thermal processes it is possible to predict power consumption of furnaces at the operational split schedule with due account of such furnace characteristics as capacity, lining materials, furnace idle times under closed and open conditions etc. The paper shows distinctions in thermal performance of acid and the basic linings in the electric-arc furnaces. The proposed approach allows to analyze thermal losses by heat conductivity and on accumulation by a refractory lining and rather accurately to determine the required balance sheet items while calculating power consumption during various periods of scrap melting for furnaces of various capacity.